2021
DOI: 10.4467/20843860pk.21.002.13456
|View full text |Cite
|
Sign up to set email alerts
|

Zarządzanie w antropocenie, czyli co w czym i co z tego. Analiza literatury dotyczącej splotu zjawisk

Abstract: Management in the Anthropocene and What Comes Out of It. Analysis of the Literature on the Entanglement of Phenomena The Anthropocene is a term that not only conjures up all kinds of images in the mind but provides an impulse to reconsider the scope of human responsibility for man-triggered processes and its place in the system of related factors on our planet. At the same time, it is a term treated by many with ambivalence, reluctance, and caution, as it often harbingers the imminent environmental doom, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The boundaries of the division between generations in different studies may slightly differ from each other. In our study the following generations can be indicated [43][44][45][46]: Instead, they are creative, active, more flexible and multi-tasking. (4) Z-born after 1995.…”
Section: Young Consumer Segmentmentioning
confidence: 99%
“…The boundaries of the division between generations in different studies may slightly differ from each other. In our study the following generations can be indicated [43][44][45][46]: Instead, they are creative, active, more flexible and multi-tasking. (4) Z-born after 1995.…”
Section: Young Consumer Segmentmentioning
confidence: 99%